IN-VIVO PHARMACOLOGICAL STUDIES OF HYPNEA MUSCIFORMIS FOUND IN THE COAST OF SAINT MARTIN ISLAND OF BANGLADESH (Bioresearch Communications, 2022)
Hypnea musciformis, a red seaweed prevalent in tropical and subtropical regions, has been linked to a multitude of therapeutic benefits. The aim of this study was to investigate the analgesic and anti-inflammatory properties of its extracts in 50% ethanol. Using the hot plate test, the acetic acid induced writhing test, and the formic acid induced test on Swiss albino mice, the analgesic potential of ethanol extracts was examined. Each test was administered at a dose of 500 mg/kg. Alternatively, an ethanol extract from carrageenan-induced paw edema was used in an anti-inflammatory experiment. Diclofenac is used as a reference standard in studies looking at the analgesic and anti-inflammatory effects of substances. In those animal models, our research demonstrates that Hypnea musciformis possesses potent anti-inflammatory and pain-relieving capabilities (percent inhibition found 28.22% on acetic acid method, 42.3% on Hot plate, and 48.7% on Formic acid).Bioresearch Commu. 9(1): 1237-1244, 2023 (January)